HUBUNGAN SELF-EFFICACY DENGAN TINGKAT KECEMASAN LANSIA PADA DIABETES MELITUS DI RUMAH SAKIT MITRA MEDIKA TANJUNG MULIA - Srilasmawanti, Srilasmawanti; Maria haryanti Butar butar; Irma Suryani (Bajang Institute, 2025)
Elderly persons with poor self-efficacy are likely to be depressed or give up quickly, are dissatisfied with their circumstances, and have a reduced ability to act. This study aimed to determine the relationship between self-efficacy and elderly anxiety level in diabetes mellitus at Mitra Medika Hospital Tanjung Mulia Medan. The correlational design was used in the study, with analytic observations made using a cross-sectional design. The purposive sampling methodology obtained 88 respondents, who were tested using the chi square method. The instrument used three categories of data: primary data, secondary data, and tertiary data, Based on the statistical results in the pearson chi-square section, the value of a simp.Sig was 0.003. Because the þ value (0.003) < α (0.05), it can be concluded that there was a significant relationship between self-efficacy and elderly anxiety level in diabetes mellitus at Mitra Medika Hospital Tanjung Mulia Medan. The results showed that there is a significant relationship between self-efficacy and diabetes mellitus at Mitra Medika Hospital Tanjung Mulia Medan. It is suggested that this research be used as input and knowledge for self-efficacy and anxiety levels, since diabetes mellitus is critical for preventing DM wounds.